Metropolitan waterworks and sewerage system a system and procedures study - Catanghal, Elena; Legaspi, Ma. Theresa; Guevara, Ma. Paz; Padua, George; Potenciano, Joan Mary (College of Engineering, 1991)
In the course of operations in a service firm, an effective and efficient systems and procedures comes in as an integral part in proper management and administration. Men, systems and processes are constantly undergoing changes and so it is necessary to develop new and better processes. in the Metropolitan Waterworks and Sewerage System (MWSS), the systems and procedures of this service-oriented firm was documented in order to develop and more efficient and effective process. The MWSS has been in existence for many decades and so the systems and procedures of the company is fairly developed and efficient. However, the analysis of the present system indicates some improvements that could be implemented in terms of work distribution, forms analysis, layout and other aspects. Analysis was done with the aid of System Flow charts, Flow Distribution charts, Work Distribution charts, Organizational charts and Office Layout. Alternatives that would help improve the system were developed and evaluated. The best alternative was specified according to the set criteria and limitations in terms of work distribution, forms design and office layout.